Aeroallergens and Asthma. Issue 4 (1994) - Chan-Yeung, Moira; Quirce, Santiago
Abstract : The main aeroallergens in both the indoor and outdoor environment that have been implicated in the pathogenesis of allergic asthma are reviewed. Pollen and fungal spores are important outdoor aeroallergens that cause sensitization in atopic subjects, leading to rhinitis and asthma in a proportion of the sensitized subjects. Each pollen type displays a particular seasonal periodicity: tree pollen are prevalent in the late winter and spring, grass in the spring and summer and weed mainly in the fall. There are regional differences in the type of pollen grains in Canada. Although the pollen grains arc large fragments less than 10 µ can reach the lower airways to cause asthma. Some fungal spores. such as Alternaria and Cladosporium, have been implicated in asthma. The full clinical impact of fungi in asthma has yet lo be clarified. With the construction of homes that are tightly scaled to conserve heat and the use or wall to wall carpet. the type and concentration of indoor aeroallergens have become increasingly different from outdoors. House dust mite and pet allergens have now been shown to he important acro:dlergcns that sensitize children in infancy and are risk factors for asthma. Clinicians should recognize the importance of aeroallergens in asthma because avoidance and/or reduc1iun of exposure is an important part of the management besides drug therapy.